2022
DOI: 10.1155/2022/8301477
|View full text |Cite|
|
Sign up to set email alerts
|

Drop Height Impacts the Lower Limb Elastic Energy’s Utilization for Male High Jumpers: A Experimental Research from Biomechanics

Abstract: The study’s objective is to clarify the influence of drop height on elastic energy’s utilization of the lower extremity, to indicate the correlations between elastic energy’s utilization and personal best, and to determine the optimal loading height for elastic energy’s utilization for male high jumpers. Ten male athletes who belong to high jump events work out the drop jump at different drop heights (0.3 m, 0.45 m, 0.6 m, and 0.75 m). Two AMTI force platforms were used to capture the dynamics data for the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Applied Bionics and Biomechanics has retracted the article titled “Drop Height Impacts the Lower Limb Elastic Energy's Utilization for Male High Jumpers: A Experimental Research from Biomechanics” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Applied Bionics and Biomechanics has retracted the article titled “Drop Height Impacts the Lower Limb Elastic Energy's Utilization for Male High Jumpers: A Experimental Research from Biomechanics” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Applied Bionics and Biomechanics has retracted the article titled "Drop Height Impacts the Lower Limb Elastic Energy's Utilization for Male High Jumpers: A Experimental Research from Biomechanics" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%